Silence as Resistance: A Postcolonial Reading of the Silence of Jonah in Jonah 4.1-11 - Ryu, Chesung Justin (Journal for the study of the Old Testament, 2009)
Established readings of the book of Jonah have criticized Jonah as the personification of a narrow-minded Jew and emphasized God’s universal and inclusive love and mercy. However, embedded in this inclusivity of universalism is a working system of exclusivity which silences the voice of the weak. Through a postcolonial reading of Jonah 4, this article explores fallacies of the established readings and suggests an alternative reading for Jonah’s anger and silence. It argues that Jonah’s anger (Jon. 4.1-11) can be recognized as legitimate given the power differential between the Israelites and the Ninevites. In addition, Jonah’s silence functions as resistance on the part of the weak over against the rhetoric of the strong, which ignores unbalanced power structures in human relationships in the name of universalism.